Densities and Apparent Molar Volume of Benzimidazole in Pure and Binary Solvent Mixtures of Ethanol + Water - Sachin S. Kale, (International Journal of Scientific Research in Science and Technology, 2024)
Benzimidazole is an important pharmacophore in medicinal chemistry. Benzimidazoles are having a many therapeutic uses like antibacterial, antifungal, analgesics, antitumor, antiparasitic, antihistamine, and antiviral. Using bicapillary pycnometer densities of Benzimidazole in ethanol with water were measured over the entire composition range at temperatures from 293.15 to 313.15 K. Densities of the saturated solution of benzimidazole in a pure and binary mixture of solvents were measured at mentioned temperature. This density data was used to calculate apparent molar volume. The apparent molar volume (
Keywords: Benzimidazole; Ethanol; Density; Apparent Molar Volume